1992
DOI: 10.1901/jaba.1992.25-671
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Variable‐ratio Reinforcement Schedule With Changing Criteria on Exercise in Obese and Nonobese Boys

Abstract: The effects of a variable-ratio schedule of reinforcement on pedaling a a stationary exercise bicycle were examined. Three obese and three nonobese 11-year-old boys were individually tested five times weekly for approximately 12 weeks. A changing-criterion design was used in which each successive criterion was increased over mean performance rate in the previous phase by approximately 15%. The contingencies of the successive criteria resulted in systematic increases in rate of exercise for all children. Final … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 19 publications
3
27
2
1
Order By: Relevance
“…The results of this study are consistent with previous studies showing that the amount of time spent exercising can be increased by providing contingencies for participating in exercise (e.g., DeLuca & Holborn, 1985, 1992Thompson & Born, 1999). Despite the clear increases in exercise that were demonstrated in this study, the possible independent effects of self-recording and contingencies were not evaluated.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of this study are consistent with previous studies showing that the amount of time spent exercising can be increased by providing contingencies for participating in exercise (e.g., DeLuca & Holborn, 1985, 1992Thompson & Born, 1999). Despite the clear increases in exercise that were demonstrated in this study, the possible independent effects of self-recording and contingencies were not evaluated.…”
Section: Discussionsupporting
confidence: 90%
“…A handful of studies have shown that reinforcement procedures can increase a broader range of behavior involved in exercise participation by adults with dementia (e.g., Thompson & Born, 1999), children and adolescents with ABI (Gurdin, Huber, & Cochran, 2005), and children with typically functioning (e.g., DeLuca & Holborn, 1985, 1992. For example, DeLuca and Holborn (1992) provided token reinforcers on variable ratio (VR) schedules that were based on the rate of revolutions peddled on a stationary bicycle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ratio (VR) (e.g., Ader & Tatum, 1961;DeLuca & Holborn, 1985;DeLuca & Holborn, 1992;Galizio, 1979;Harzem, Lowe, & Bagshaw, 1978;Hayes, Brownstein, Haas & Greenway, 1986;Joyce & Chase, 1990;Kudadjie-Gyamfi & Rachlin, 2002;Matthews, Shimoff, Catania, & Sagvolden, 1977;Shimoff, Catania, & Matthews, 1981;Weiner, 1970;Wulfert, Greenway, Farkas, Hayes, Dougher, 1994). This has led to rigorous attention to the implementation of instructions, for they can not only affect contingency-shaped behaviour, but also disguise schedule sensitivity (Hayes, Brownstein, Zettle, Rosenfarb, & Korn, 1986).…”
Section: Extinction Of Transferred Avoidance Functions 29mentioning
confidence: 99%
“…Um exemplo do emprego do delineamento de mudança de critério (figura adaptada de De Luca & Holborn, 1992). LB = linha de base ou condição controle.…”
Section: Delineamento De Mudança De Critériounclassified